Juvenile Spider Mites Induce Salicylate Defenses, but Not Jasmonate Defenses, Unlike Adults - Liu, Jie; Legarrea, Saioa; Alba, Juan M.; Dong, Lin; Chafi, Rachid; Menken, Steph B. J.; Kant, Merijn R. (Frontiers in Plant Science, 2020)
When plants detect herbivores they strengthen their defenses. As a consequence, some herbivores evolved the means to suppress these defenses. Research on induction and suppression of plant defenses usually makes use of particular life stages of herbivores. Yet many herbivorous arthropods go through development cycles in which their successive stages have different characteristics and lifestyles. Here we investigated the interaction between tomato defenses and different herbivore developmental stages using two herbivorous spider mites, i.e., Tetranychus urticae of which the adult females induce defenses and T. evansi of which the adult females suppress defenses in Solanum lycopersicum (tomato). First, we monitored egg-to-adult developmental time on tomato wild type (WT) and the mutant defenseless-1 (def-1, unable to produce jasmonate-(JA)-defenses). Then we assessed expression of salivary effector genes (effector 28, 84, SHOT2b and SHOT3b) in the consecutive spider mite life stages as well as adult males and females. Finally, we assessed the extent to which tomato plants upregulate JA- and salicylate-(SA)-defenses in response to the consecutive mite developmental stages and to the two sexes. The consecutive juvenile mite stages did not induce JA defenses and, accordingly, egg-to-adult development on WT and def-1 did not differ for either mite species. Their eggs however appeared to suppress the SA-response. In contrast, all the consecutive feeding stages upregulated SA-defenses with the strongest induction by T. urticae larvae. Expression of effector genes was higher in the later developmental stages. Comparing expression in adult males and females revealed a striking pattern: while expression of effector 84 and SHOT3b was higher in T. urticae females than in males, this was the opposite for T. evansi. We also observed T. urticae females to upregulate tomato defenses, while T. evansi females did not. In addition, of both species also the males did not upregulate defenses. Hence, we argue that mite ontogenetic niche shifts and stage-specific composition of salivary secreted proteins probably together determine the course and efficiency of induced tomato defenses.